Poverty Traps - Hoff, Karla, 1953-; Durlauf, Steven N.; Bowles, Samuel (Book collections on Project MUSE., 2006)
Much popular belief--and public policy--rests on the idea that those born into poverty have it in their power to escape. But the persistence of poverty and ever-growing economic inequality around the world have led many economists to seriously question the model of individual economic self-determination when it comes to the poor. In Poverty Traps, Samuel Bowles, Steven Durlauf, Karla Hoff, and the book's other contributors argue that there are many conditions that may trap individuals, groups, and whole economies in intractable poverty. For the first time the editors have brought tog.